Design analysis of TMJ implant under physiological loading condition - Arabshahi, Zohreh (2012)
The aim of this study was to determine the behavior of Temporomandibular joint implant made of different materials when it is subjected to loads resulted of daily movements. A three dimensional model of a lower mandible of a human were developed from a CT scan dataset. A commercial Temporomandibular joint implant and fixation screws were modeled. Three dimensional finite element models of implanted mandible analyzed under static loading of five clunching tasks. The investigation went to study on two materials of titanium and Cobalt-chromium alloy for implant. The equivalent strain of whole structure was computed and utilized for evaluation of implant design. The safety factor results showed that both materials were capable to carry the applied complex loads.